Dakwah Kultural: Analisis Strategi Islamisasi Sunan Kalijaga Melalui Budaya Lokal - Sofia Nofita Sari; Rohima Khoirunnisa; Zidni Nur Fatimah; Raha Bistara (STAI Darul Kamal NW Kembang Kerang, 2026)
This study examines the da’wah strategy of Sunan Kalijaga, one of the prominent members of the Walisongo, who played a crucial role in the Islamization process in Java. The research focuses on his cultural approach through the use of arts and local traditions such as wayang kulit, tembang, gamelan, the Sekaten ceremony, and other Javanese customs. Employing a qualitative method with a library research approach, this study explores the historical background and relevance of Sunan Kalijaga’s da’wah within the perspective of the Qur’an and Hadith. The findings reveal that his cultural approach effectively conveyed Islamic values persuasively and harmoniously, making them acceptable to the Javanese society that was predominantly influenced by Hindu-Buddhist traditions. The messages of da’wah included aspects of aqidah, sharia, and akhlaq, all integrated into local cultural expressions. Sunan Kalijaga’s strategies remain highly relevant as an inspiration for contemporary da’wah practices in Indonesia’s multicultural society